(untitled) - Collette, Bruce B (Rome, 1983)
It provides a comprehensive key to genera and species, preceeded by an illustrated glossary of technical terms and measurements. The systematic part of the catalogue includes a drawing and a distribution map for each species, a list of scientific and vernacular species names and 1wide-ranging information on habitat, bioloy, and fisheries.
Keywords: Scombridae